2010
DOI: 10.1038/pj.2010.33
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ultrafine uniform electrospun polyimide nanofiber

Abstract: This paper reports the preparation of bead-free ultrafine uniform nanofibers with a narrow fiber diameter distribution from fluorinated polyimide by electrospinning. Increasing the electrical conductivity of polymer solutions by the addition of salts and decreasing the discharge rate of water from the polymer by decreasing the humidity in the surrounding air decreases the diameter of the electrospun nanofiber. Ultrafine uniform nanofibers were achieved using these new salt and humidity conditions, and we succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…These results suggested that the fine morphology of the electrospun fibers can be successfully created by the proper modulation of the solution properties; similar results have also been reported by other researchers. 9,17,[19][20][21][22][23][24][25] The Fourier-transform infrared spectra of the electrospun CA fibers showed a strong ester carbonyl stretching vibration at 1750 cm À1 , 26 whereas those of PEO fibers exhibited strong peaks at 2900 cm À1 that were attributed to the molecular stretching of methylene groups (CH 2 ). 9 The Fourier-transform infrared spectra of the CA-PEO fibers exhibited both of these characteristic peaks, as shown in Figure 4.…”
Section: Effects Of Peo and Zno Nps On Ca Nanocomposite Film C Pittarmentioning
confidence: 99%
“…These results suggested that the fine morphology of the electrospun fibers can be successfully created by the proper modulation of the solution properties; similar results have also been reported by other researchers. 9,17,[19][20][21][22][23][24][25] The Fourier-transform infrared spectra of the electrospun CA fibers showed a strong ester carbonyl stretching vibration at 1750 cm À1 , 26 whereas those of PEO fibers exhibited strong peaks at 2900 cm À1 that were attributed to the molecular stretching of methylene groups (CH 2 ). 9 The Fourier-transform infrared spectra of the CA-PEO fibers exhibited both of these characteristic peaks, as shown in Figure 4.…”
Section: Effects Of Peo and Zno Nps On Ca Nanocomposite Film C Pittarmentioning
confidence: 99%
“…The other appropriate electrospinning conditions, including applied voltages, feeding rate, distance between the spinneret and the collector, and relative humidity, were 15-30 kV, 0.12-1.2 ml hr À1 , 10-20 cm and 5-10% relative humidity, respectively. 13,14,16,17 It was also found that using a polymer concentration that was too low or too high gave mixtures of nanofibers and beads or thick fibers, respectively. On the basis of our knowledge, the optimal electrospinning conditions for 6FDA-APPS, PSF and PAN were carefully studied.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12] We have succeeded in preparing uniform non-beaded nanofibers with diameters of B30 nm by controlling the processing parameters, including applied voltage, feed rate, electrospinning humidity, and polymer solution viscosity and electrical conductivity. 13,14 The productivity of nanofibers by the electrospinning method is sufficiently high to supply industrial applications by using non-nozzle type spinnerets and/or rotary drum collectors. The configuration of nanofiber assembly can also be controlled from nonwoven nanofibrous membranes to aligned nanofibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials have attracted much interest for use as sensors, filters and tissue engineering scaffolds, and drug delivery membranes, among other applications. [12][13][14][15][16][17] In the electrospinning process, a viscous, entangled polymer solution is ejected through a syringe toward a grounded target under the application of a high electric potential (typically 10-30 kV). The droplet of solution stretches into a thin jet during flight, and solvent evaporates rapidly from the jet, reducing its diameter and increasing the charge density on the surface.…”
Section: Introductionmentioning
confidence: 99%